ANALYSIS OF THE IMPACT AND BENEFITS OF TECHNOLOGY TRENDS IN GLOBAL ACCESSIBILITY AND CUSTOMIZED LEARNING - Nur Latifah; Baskoro Ajie (International Journal of Teaching and Learning, 2026)
In the digital era, technology plays a vital role in increasing global accessibility in various fields, especially in education. This study analyzes the influence of technological trends, such as artificial intelligence, machine learning, and virtual reality, in creating a more inclusive and accessible learning system for various groups. The results of the study show that technology is able to overcome geographical, economic, and social barriers in education, providing opportunities for individuals from various backgrounds to access learning materials more flexibly. In addition, technology also increases the effectiveness of learning by providing a more interactive and personalized experience according to user needs. Thus, the use of technology in learning not only expands access but also improves the quality of education globally.